A New Approach to Develop Resistant Cultivars Against the Plant Pathogens: CRISPR Drives - Tek, Mumin Ibrahim; Budak, Kubra (Frontiers in Plant Science, 2022)
CRISPR drive is a recent and robust tool that allows durable genetic manipulation of the population. One of this technology's most extensive and controversial uses is the control of human disease vectors such as malaria vector mosquitos. However, in recent years, it has been suggested that CRISPR drives can also be used to control plant diseases, pests, and weeds. Studies and perspectives aim to change the population structure by releasing individuals carrying CRISPR drive into the pest population. However, using a CRISPR drive in Arabidopsis for the first time in 2021 has been shown to use this technology in plant breeding to obtain homozygous parental lines. This perspective has proposed using CRISPR drive to develop pathogen-resistant cultivars by disrupting susceptibility-gene (S). In the breeding program, CRISPR is used to create S-gene mutations on two parental lines of hybrid cultivars. However, CRISPR must be reapplied or long-term backcross for the parental line to obtain homozygous S-mutant cultivars. When a parental line cross with different parental lines to develop new hybrids, heterozygous S-mutations could not resist in hybrid against the pathogen. CRISPR drives are theoretically valid to develop homozygous S-mutant plants against pathogens by only routine pollination after CRISPR drive transformation to just one parental line. This way, breeders could use this parental line in different crossing combinations without reapplying the genome-editing technique or backcrossing. Moreover, CRISPR drive also could allow the development of marker-free resistant cultivars with modifications on the drive-cassette.